Effects of a sucralfate-containing ointment on quality of life and symptoms associated with hemorrhoidal disease: patient-reported results of a Slovakian, pharmacist-led observational survey - Snopková, Miroslava; Sukel‘, Ondrej; Micanko, Jan (Frontiers in Gastroenterology, 2023)
Purpose This pharmacist-led study evaluated the effect of a rectal ointment containing sucralfate on quality of life, symptom frequency and time to relief of symptoms in Slovakian individuals with hemorrhoidal disease (HD). Methods The multicenter prospective survey was conducted at 45 community pharmacies in Slovakia. Pharmacists invited adults (≥18 years) using sucralfate-containing ointment for their HD-related symptoms to participate. Results 241 patients completed the HEMO-FISS-QoL questionnaire and a survey of symptom frequency at the beginning and end of the 14-day survey period. The primary endpoint was the change in HEMO-FISS-QoL scores in patients with hemorrhoidal symptoms during the 7 days before the initial pharmacy visit. Of the 241 patients enrolled in the survey, 144 had experienced hemorrhoidal symptoms within the preceding 7 days (mean age 51 years; 59.0% female). For these 144 patients, the total HEMO-FISS-QoL score decreased (i.e., quality of life was improved) from baseline by a mean of –8.7 (95% confidence interval –12.6, –6.2; P<0.001) at day 14. The frequency of hemorrhoidal symptoms was significantly reduced (P<0.001 vs baseline). Symptom relief was rapid; at 1-hour post-treatment 54.6% of patients had relief from pain and 56.3% from itching, and by 24 hours post-treatment most patients had relief from these symptoms (77.2% and 73.0%, respectively). No incidents nor adverse events related to sucralfate-containing ointment were reported to pharmacists. Conclusion The results of this pharmacist-led observational survey suggest that the sucralfate-containing ointment could improve quality of life in patients with HD, providing rapid relief with a good safety profile. To confirm these results in a larger, well-defined patient population, randomized controlled trials in patients with clinically diagnosed HD are warranted.